The Role of the Prosecutor as Dominus Litis in Assertive and Humanistic Law Enforcement - Nugrah Gables Manery; Rocky S Mantaiborbir (International Forum of Researchers and Lecturers, 2025)
Law enforcement holds a central role in shaping social order and ensuring the effective implementation of legal functions in Indonesia. The law is not merely a normative reference but must be strategically positioned as the fundamental basis for resolving disputes and conflicts that emerge within society. In this regard, Law No. 16 of 2004 concerning the Indonesian Prosecutor’s Office, particularly Article 2 paragraph (1), clearly stipulates that the Prosecutor’s Office is a state institution entrusted with exercising governmental authority in the field of prosecution, along with other responsibilities mandated by law. Within the framework of criminal justice, the Prosecutor’s Office assumes a pivotal role as Dominus Litis—the ultimate controller of criminal cases. This authority signifies that the Prosecutor’s Office is the only institution empowered to decide whether a particular case, supported by sufficient evidence in line with the Criminal Procedure Code, is eligible to be brought before the court. The prosecutor’s discretionary power in this context highlights its critical position in upholding justice and maintaining the integrity of legal proceedings. Beyond its prosecutorial function, the Prosecutor’s Office also bears the exclusive responsibility for executing criminal judgments, ensuring that court decisions are implemented properly and consistently with the rule of law. This dual function—both as Dominus Litis and executor of judicial decisions—underlines the institutional indispensability of the Prosecutor’s Office in the Indonesian legal system. The institution’s authority is therefore not limited to initiating prosecutions but also extends to safeguarding the finality and enforcement of criminal verdicts, which makes it a cornerstone in the broader architecture of law enforcement. Consequently, strengthening the role and capacity of the Prosecutor’s Office is essential for advancing justice, protecting the rights of citizens, and reinforcing the legitimacy of Indonesia’s legal order.